Development of LED cubes - Chen, Zhenzhong (2018)
This article is aimed to design LED Cubes as a educational tool to demonstrate some basic physical principles and phenomena to students in classes. First, we illustrate the materials, chips, structure and softwares in making LED cubes. Then, we will explain the design and the principles of each LED cube. After this, we will control every LED to light up in different color and intensity, which is aimed to guarantee we can design certain animation. After finishing one LED cube, we will continue to parallel eight 8x8x8 LED cubes together to become one 16x16x16 LED cube. And after accomplishing this hardware-level connection, we will further research ways to make them cooperate. So, we will explore different ways to make them communicate and cooperate to each other with the assiatance of computer.